Genetıc dıversıty and relatıonshıp among sıx wıld corchorus specıes by rapd and SSR analysıs - Afroz, Mahın; Sultana, Syeda Sharmeen; Sarker, Rakha Harı (Bangladesh Journal of Botany, 2025)
In this investigation thirteen RAPD and eight SSR primers were used that generated 69 and 27 loci with 100% and 96.30% polymorphism, respectively for six wild Corchorus species viz. C. brevicornatus, C. septentrionalis, C. urticifolius, C. hirtus, C. siliquosus and C. pinnatipartitus. After RAPD analysis, C. septentrionalis is distantly related from other 5 wild species and formed a separate cluster at the highest genetic distance with C. pinnatipartitus (1.1431). On the other hand, C. hirtus and C. pinnatipartitus are close to each other at the lowest genetic distance 0.2638. SSR analysis showed C. urticifolius is distantly related from other 5 wild species and formed a separate cluster at highest genetic distance with C. septentrionalis (1.3499) while, C. siliquosus and C. pinnatipartitus were close to each other at the lowest genetic distance 0.0770. Therefore, genetic diversity and relationship among 6 wild Corchorus species could be analyzed authentically by RAPD and SSR analysis. Bangladesh J. Bot. 54(3): 525-530, 2025 (September)